Policing advance fee fraud (AFF): Experiences of fraud detectives using a victim-focused approach - Webster, Julianne (International journal of police science & management, 2017)
Advance fee fraud (AFF) involves an offender using deceit to obtain a financial gain from the victim. The victim believes that by forwarding a sum of money, there will be a future ‘pay-off’. The most commonly witnessed forms of AFF perpetrated via the Internet include classic ‘Nigerian’ or ‘419’ scams, investment fraud and romance fraud. Because of the largely transnational nature of AFF offending, where the victim and offender typically reside in different parts of the world, police are adapting their traditional and reactive approaches to more innovative strategies to combat this crime more effectively. This article utilises a qualitative, semi-structured interview design to explore the experiences of police detectives involved in the implementation of an early intervention model with victims of AFF. The study highlights the challenges involved in developing effective police strategies to proactively reduce the duration and severity of this type of financial victimisation.